The Experiences of International Doctoral Students During the COVID-19 Lockdown - Sánchez King, Juan Pablo A.; Dahal, Sanjeev (Journal of Interdisciplinary Studies in Education, 2022)
This study explored the impact of the COVID-19 lockdown on international doctoral students at a US university. It elicited narratives of coping with the lockdown and stress-reducing resources and strategies. The lockdown allowed students to focus on their work, and additional household and child caregiving roles required students to develop innovative coping practices. It also forced students without adequate social networks and community integration to experience more uncertainties. All respondents experienced strong disrupted emotions, e.g., anxiety and sadness. Social closeness was an effective stress antidote. Universities should create programs to expand and nurture students' social networks aligned with their interests and needs. Health policies and programs aimed at preventing and treating stress and burnout among doctoral students should focus on their social environment.